A gravitationally lensed quasar discovered in OGLE. Issue 1 (1st February 2018) - Kostrzewa-Rutkowska, Zuzanna; Kozłowski, Szymon; Lemon, Cameron; Anguita, T; Greiner, J; Auger, M W; Wyrzykowski, Ł; Apostolovski, Y; Bolmer, J; Udalski, A; Szymański, M K; Soszyński, I; et al.
Abstract: We report the discovery of a new gravitationally lensed quasar (double) from the Optical Gravitational Lensing Experiment (OGLE) identified inside the ∼670deg 2 area encompassing the Magellanic Clouds. The source was selected as one of ∼60 'red W 1 −  W 2' mid-infrared objects from WISE and having a significant amount of variability in OGLE for both two (or more) nearby sources. This is the first detection of a gravitational lens, where the discovery is made 'the other way around', meaning we first measured the time delay between the two lensed quasar images of −132 <  t AB  < −76  d (90 per cent CL), with the median t AB ≈ −102  d (in the observer frame), and where the fainter image B lags image A. The system consists of the two quasar images separated by 1.5 arcsec on the sky, with I ≈ 20.0 mag and I ≈ 19.6 mag, respectively, and a lensing galaxy that becomes detectable as I ≈ 21.5 mag source, 1.0 arcsec from image A, after subtracting the two lensed images. Both quasar images show clear AGN broad emission lines at z  = 2.16 in the New Technology Telescope spectra. The spectral energy distribution (SED) fitting with the fixed source redshift provided the estimate of the lensing galaxy redshift of z ≈ 0.9 ± 0.2 (90 per cent CL), while its type is more likely to be elliptical (the SED-inferred and lens-model stellar mass is more likely present in ellipticals) than spiral (preferred redshift by the lens model).